Step * 1 of Lemma mean-value-theorem


1. : ℝ
2. : ℝ
3. a < b
4. ∀f,f':[a, b] ⟶ℝ.
     (f'[x] continuous for x ∈ [a, b]
      d(f[x])/dx = λx.f'[x] on [a, b]
      (f[a] f[b])
      (∀e:ℝ((r0 < e)  (∃x:ℝ((x ∈ [a, b]) ∧ (|f'[x]| ≤ e))))))
5. [a, b] ⟶ℝ
6. f' [a, b] ⟶ℝ
7. f'[x] continuous for x ∈ [a, b]
8. d(f[x])/dx = λx.f'[x] on [a, b]
9. : ℝ
10. r0 < e
⊢ ∃x:ℝ((x ∈ [a, b]) ∧ (|f[b] f[a] f'[x] (b a)| ≤ e))
BY
(InstHyp [⌜λ2x.((f[b] f[a]) (x a)) (b a) f[x]⌝
                ;⌜λ2x.f[b] f[a] (b a) f'[x]⌝4⋅
   THEN Auto
   }

1
.....antecedent..... 
1. : ℝ
2. : ℝ
3. a < b
4. ∀f,f':[a, b] ⟶ℝ.
     (f'[x] continuous for x ∈ [a, b]
      d(f[x])/dx = λx.f'[x] on [a, b]
      (f[a] f[b])
      (∀e:ℝ((r0 < e)  (∃x:ℝ((x ∈ [a, b]) ∧ (|f'[x]| ≤ e))))))
5. [a, b] ⟶ℝ
6. f' [a, b] ⟶ℝ
7. f'[x] continuous for x ∈ [a, b]
8. d(f[x])/dx = λx.f'[x] on [a, b]
9. : ℝ
10. r0 < e
⊢ f[b] f[a] (b a) f'[x] continuous for x ∈ [a, b]

2
.....antecedent..... 
1. : ℝ
2. : ℝ
3. a < b
4. ∀f,f':[a, b] ⟶ℝ.
     (f'[x] continuous for x ∈ [a, b]
      d(f[x])/dx = λx.f'[x] on [a, b]
      (f[a] f[b])
      (∀e:ℝ((r0 < e)  (∃x:ℝ((x ∈ [a, b]) ∧ (|f'[x]| ≤ e))))))
5. [a, b] ⟶ℝ
6. f' [a, b] ⟶ℝ
7. f'[x] continuous for x ∈ [a, b]
8. d(f[x])/dx = λx.f'[x] on [a, b]
9. : ℝ
10. r0 < e
⊢ d(((f[b] f[a]) (x a)) (b a) f[x])/dx = λx.f[b] f[a] (b a) f'[x] on [a, b]

3
1. : ℝ
2. : ℝ
3. a < b
4. ∀f,f':[a, b] ⟶ℝ.
     (f'[x] continuous for x ∈ [a, b]
      d(f[x])/dx = λx.f'[x] on [a, b]
      (f[a] f[b])
      (∀e:ℝ((r0 < e)  (∃x:ℝ((x ∈ [a, b]) ∧ (|f'[x]| ≤ e))))))
5. [a, b] ⟶ℝ
6. f' [a, b] ⟶ℝ
7. f'[x] continuous for x ∈ [a, b]
8. d(f[x])/dx = λx.f'[x] on [a, b]
9. : ℝ
10. r0 < e
11. ∀e:ℝ((r0 < e)  (∃x:ℝ((x ∈ [a, b]) ∧ (|f[b] f[a] (b a) f'[x]| ≤ e))))
⊢ ∃x:ℝ((x ∈ [a, b]) ∧ (|f[b] f[a] f'[x] (b a)| ≤ e))


Latex:


Latex:

1.  a  :  \mBbbR{}
2.  b  :  \mBbbR{}
3.  a  <  b
4.  \mforall{}f,f':[a,  b]  {}\mrightarrow{}\mBbbR{}.
          (f'[x]  continuous  for  x  \mmember{}  [a,  b]
          {}\mRightarrow{}  d(f[x])/dx  =  \mlambda{}x.f'[x]  on  [a,  b]
          {}\mRightarrow{}  (f[a]  =  f[b])
          {}\mRightarrow{}  (\mforall{}e:\mBbbR{}.  ((r0  <  e)  {}\mRightarrow{}  (\mexists{}x:\mBbbR{}.  ((x  \mmember{}  [a,  b])  \mwedge{}  (|f'[x]|  \mleq{}  e))))))
5.  f  :  [a,  b]  {}\mrightarrow{}\mBbbR{}
6.  f'  :  [a,  b]  {}\mrightarrow{}\mBbbR{}
7.  f'[x]  continuous  for  x  \mmember{}  [a,  b]
8.  d(f[x])/dx  =  \mlambda{}x.f'[x]  on  [a,  b]
9.  e  :  \mBbbR{}
10.  r0  <  e
\mvdash{}  \mexists{}x:\mBbbR{}.  ((x  \mmember{}  [a,  b])  \mwedge{}  (|f[b]  -  f[a]  -  f'[x]  *  (b  -  a)|  \mleq{}  e))


By


Latex:
(InstHyp  [\mkleeneopen{}\mlambda{}\msubtwo{}x.((f[b]  -  f[a])  *  (x  -  a))  -  (b  -  a)  *  f[x]\mkleeneclose{}
                            ;\mkleeneopen{}\mlambda{}\msubtwo{}x.f[b]  -  f[a]  -  (b  -  a)  *  f'[x]\mkleeneclose{}]  4\mcdot{}
  THEN  Auto
  )




Home Index